Improving stunting prevention program through community healthcare workers training and home-based growth monitoring: A quality improvement model - Miranda, Adriana Viola; Nugraha, Ryan Rachmad; Sirmareza, Trio; Rastuti, Maritta; Asmara, Rindang; Astuti, Sri Puji; Nasytha, Safarah Risvie; Petersen, Zack (Paediatrica Indonesiana, 2024)
Background Over 1.5 million community healthcare workers (CHWs) work in pos pelayanan terpadu (posyandu) in Indonesia. They are in charge of growth monitoring and counseling, as part of a community-based stunting prevention program. Recent literature suggests that the program requires quality improvements to maximize its potential. Objective To understand the impacts of a quality improvement model comprising capacity building for CHWs and home-based growth monitoring using smart charts on posyandu performance, particularly related on its stunting prevention components. Methods This cross-sectional study was conducted in two rural villages in Lombok, Indonesia in May 2023. We interviewed 130 CHWs and 317 mothers with children under-five with a pre-validated questionnaire on posyandu performance that was developed using an input-process-output framework. We evaluated the CHWs dan mothers performances in the height measurement and counseling process. Results Both CHWs and mothers perceived performance improvements in the height measurement and counseling processes, with statistically significant differences between pre- and post-intervention performance scores for height measurement [mean differences of 0.38 points; 95%CI 0.188 to 0.566; P<0.000 (CHWs) and 0.276 points; 95%CI 0.469 to 0.846; P<0.000 (mothers)]; for counseling [mean differences of 0.285 points; 95%CI 0.149 to 0.42; P<0.001 (CHWs) and 0.142 points; 95%CI 0.098 to 0.186; P<0.000 (mothers)]. Performance improvements were also found across all posyandu components, including those related to stunting. Conclusion Capacity building for CHWs and home-based growth monitoring using smart charts are beneficial in improving community-based stunting prevention programs.